Case Report on Benign Spindle Cell Tumour - Rohini D. Ambadkar, Indu Alwadkar, Roshan Umate (Drugs and Cell Therapies in Hematology, 2021)
Benign spindle cell lesions of the breast encompass a wide and heterogeneous spectrum of fibroblastic and myofibroblastic tumor-like or tumor entities. By definition, they are composed exclusively of spindle cells (pure spindle cell lesions), with no mixed epithelial component.Spindle cell carcinoma, also known as carcinosarcoma, pseudosarcoma, polypoid carcinoma, sarcomatoid carcinoma, and the spindle cell variation of squamous cell carcinoma, is a rare kind of malignant tumour that appears as a polypoid exophytic lesion. Spindle cell sarcoma is a type of cancer. Spindle cell sarcoma is a malignant (cancerous) tumour that can arise in the bone or soft tissue. It can affect any region of the body, although the limbs are the most prevalent (arms and legs). Clinical Finding: A 2-year-old male patient was admitted to AVBRH in May 2021 with complaints of edema, nausea, and vomiting and massive abdominal swelling. Diagnostic Evaluation: HB-6.7, TLC:-16, 200, PLT:-15, 000, MCV:-67.0, SR. BILIRUBIN:-0.7 Therapeutic Intervention – Tab. Allopuraznol 300mg BD, Inj. Emset:- 1.8mg TDS. Inj. Pantop 12mg BD, Inj. Ceftraxon 20ml NS 1 mg BD. Outcomes- Spindle cell tumors are rare tumors that arise most commonly from the peripheral and deep soft tissues. It can present as a large abdominal mass. Our case presented with abdominal distention. CT scan showed a large mass occupying the whole abdomen and pelvis. The patient is admitted to AVBRH and getting palliative medical and nursing care. Conclusion : A thorough careful surgical and chemotherapy plan is required to treat such a massive tumour and multidisciplinary team efforts can be fruitful for better prognosis.